International institute of tropical agriculture plantain and banana programme: an insight into the contributions of farmerto farmer extension paradigm - Faturoti, B.O.; Agwu, Agwu E.; Igbokwe, E.M.; Tenkouano, A. (2008)
Dissemination of research results by the International Institute of Tropical Agriculture (IITA) had been a major challenge to the Institute as inappropriate dissemination mechanism was revealed as a major constraint to her earlier efforts in disseminating cooking banana technologies between 1990 and 1994. A public-private technology delivery approach (research-farmer-to-farmer extension approach), which allows farmers to play the major role in dissemination of IITA plantain and banana based technologies was undertaken in three states of Nigeria. This study provides an insight into the contributions of this paradigm shift. The results show that farmer-to-farmer dissemination accounted for 26.6% awareness and 35.7% source of solutions to problems encountered in technology adoption at no direct cost to research and extension. Average plantain and banana hybrid adoption in the three states was 50.7%.Correlation analysis revealed that household size, ever questioned about plantain production problems, frequency of extension visits and trial experience had significant relationships with adoption. The regression analysis indicated that trial experience was the only variable with predictive value for plantain and banana hybrids adoption (R = 0.21). We concluded that free flow of information among all stakeholders is the panacea for sustained adoption and diffusion of the IITA plantain and banana based innovations.